TDP-43 mediates SREBF2-regulated gene expression required for oligodendrocyte myelination - Ho, Wan Yun; Chang, Jer-Cherng; Lim, Kenneth; Cazenave-Gassiot, Amaury; Nguyen, Aivi T.; Foo, Juat Chin; Muralidharan, Sneha; Viera-Ortiz, Ashley; Ong, Sarah J.M.; Hor, Jin Hui; Agrawal, Ira; Hoon, Shawn; et al. (The Journal of cell biology, 2021)
Cholesterol metabolism operates autonomously within the central nervous system (CNS), where the majority of cholesterol resides in myelin. We demonstrate that TDP-43, the pathological signature protein for amyotrophic lateral sclerosis (ALS) and frontotemporal dementia (FTD), influences cholesterol metabolism in oligodendrocytes. TDP-43 binds directly to mRNA of SREBF2, the master transcription regulator for cholesterol metabolism, and multiple mRNAs encoding proteins responsible for cholesterol biosynthesis and uptake, including HMGCR, HMGCS1, and LDLR. TDP-43 depletion leads to reduced SREBF2 and LDLR expression, and cholesterol levels in vitro and in vivo. TDP-43–mediated changes in cholesterol levels can be restored by reintroducing SREBF2 or LDLR. Additionally, cholesterol supplementation rescues demyelination caused by TDP-43 deletion. Furthermore, oligodendrocytes harboring TDP-43 pathology from FTD patients show reduced HMGCR and HMGCS1, and coaggregation of LDLR and TDP-43. Collectively, our results indicate that TDP-43 plays a role in cholesterol homeostasis in oligodendrocytes, and cholesterol dysmetabolism may be implicated in TDP-43 proteinopathies–related diseases.